2016
DOI: 10.1021/acs.jpclett.6b01103
|View full text |Cite
|
Sign up to set email alerts
|

Direct Addition Mechanism during the Catalytic Hydrogenation of Olefins over Platinum Surfaces

Abstract: The mechanism of the hydrogenation of olefins catalyzed by metal surfaces was probed by using isotope labeling in conjunction with a high-flux effusive molecular beam setup capable of sustaining steady-state conversion under well-controlled ultrahigh vacuum (UHV). The unique conditions afforded by this instrument, namely, a single collision regime and impinging frequencies equivalent to pressures in the mTorr range, led to the clear identification of two competing pathways: a multiple H-D isotope exchange chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…2325 The formation of hydrogenation products would require the addition of two surface Pd–H to di- σ -Pd alkyl intermediate B . 42 The presence of thiolate ligands on PdNP surface would make this direct hydrogenation process kinetically slower than the process requiring the addition of only single Pd–H. Both the isomerization and hydrogenolysis products are generated from mono- σ -Pd alkyl intermediate C after the coordination of alkene group on PdNP surface ( A ).…”
Section: Resultsmentioning
confidence: 99%
“…2325 The formation of hydrogenation products would require the addition of two surface Pd–H to di- σ -Pd alkyl intermediate B . 42 The presence of thiolate ligands on PdNP surface would make this direct hydrogenation process kinetically slower than the process requiring the addition of only single Pd–H. Both the isomerization and hydrogenolysis products are generated from mono- σ -Pd alkyl intermediate C after the coordination of alkene group on PdNP surface ( A ).…”
Section: Resultsmentioning
confidence: 99%
“…The experiments reported in this Letter were carried out by using an effusive but collimated molecular beam directed at a model platinum surface under a well-controlled ultrahigh vacuum (UHV) environment . It is in general difficult to sustain catalytic hydrogenation reactions under vacuum, but we have recently developed a high-flux beam setup that affords this type of studies. Our arrangement is based on a single capillary tube capable of delivering fluxes equivalent to pressures in the mTorr to Torr range on the surface and on using mass spectrometry for the detection of the reactants and products. Data from a typical run for the room-temperature (300 K) hydrogenation of crotonaldehyde promoted by a polycrystalline Pt disk, obtained with that setup, are reported in Figure .…”
mentioning
confidence: 99%
“…The previous studies confirmed the contribution of the p orbitals and planar geometry of the benzene ring in aiding the formation of the di-σ-bonded Pd-alkyl intermediate that is necessary for the hydrogenation process. 26,33,34 To further investigate alkanethiolate-capped PdNP as chemoselective hydrogenation catalysts, m -nitrostyrene was first selected as a control system (Scheme 1). Because the nitro moiety is strongly electron-withdrawing and in general very reactive to Pd catalysts under a hydrogen environment, it was necessary to determine the optimized conditions that provide an efficient hydrogenation activity for less activated alkenes while maintaining high chemoselectivity for hydrogenation of alkene over the nitro group.…”
Section: Resultsmentioning
confidence: 99%